The potential adverse effect of energy drinks on executive functions in early adolescence - Van Batenburg-Eddes, Tamara; Lee, Nikki C.; Weeda, Wouter D.; Krabbendam, Lydia; Huizinga, Mariette (Frontiers in Psychology, 2014)
Introduction. Manufacturers of energy drinks (EDs) claim their products improve cognitive performance. Young adolescents are in a critical developmental phase. The impact of ED intake on their development is not yet clear. Therefore, we studied the associations of both caffeine intake and ED consumption with executive functions (EFs), and the role of pubertal status and sleeping problems. Methods. A sample of 509 participants (mean age: 13.1 years, SD 0.85) participated in the study. The level of pubertal development was classified in five pubertal status categories. Participants were asked to report their caffeine (for example coffee) and ED consumption for each day of the week. In addition, they indicated sleep quality by reporting problems falling asleep or waking up and/or interrupted sleep. EFs were assessed by self- and parent reports of the Behavior Rating Inventory of Executive Function (BRIEF). Results. Consuming on average one or more ED(s) a day was associated with more problems in self-reported behavior regulation and metacognition, and with more problems in parent-reported metacognition. Only high caffeine consumption (two or more cups a day) was associated with parent-reported problems with metacognition. The sum of caffeine and ED use was associated with a higher amount of problems with self-reported metacognition and parent reported behavior regulation. The effect estimates for the association between caffeine and ED use combined and EFs did not exceed those of EDs or caffeine separately. Adjusting for pubertal status, gender, educational level, number of sleeping problems and hours of sleep did not change the effect estimates substantially. Conclusion. The observed associations between ED consumption and EFs suggest that regular consumption of EDs - even in moderate amounts – may have a negative impact on daily life behaviors related to EF in young adolescents.